Additive manufacturing technologies from an optimization perspective - Kumar, K. (Kaushik), 1968-; Zindani, Divya, 1989-; Davim, J. Paulo (Engineering Science Reference, 2019)
"This book examines the latest advances in next-generation manufacturing. It explores the basic and applied knowledge of additive manufacturing"--